Gambaran Sosial Ekonomi Pada Keluarga Dengan Penyakit Kronis - Prabarini, Lintang Puspita; Annisa Rahmi Galleryzki; Sekarini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Chronic disease is a source of the highest stress, not only the patient but also involves the entire family. The burden of chronic disease has had an impact on the psychosocial and financial conditions of families. This research aims to determine the psychosocial and economic impact on families with chronic diseases. The research is a descriptive-observative study with a cross-sectional approach. The research sample consisted of 120 people selected through a screened sampling approach. The research results showed that 51.7% of respondents felt a decrease in income due to chronic illness and borrowed money to meet their needs. The most felt psychosocial impacts were reduced participation in social activities (60%) and changes in communication patterns within the family (55%). The majority of respondents also felt an increase in closeness between family members due to the care process provided (75%). This research concludes that the socio-economic conditions of families can change due to family members experiencing chronic illnesses, therefore nurses have an important role in providing support to patients and families to adapt to these conditions.